Exclusive Breastfeeding and Child Sleep Quality During and After the COVID-19 Pandemic in Samarinda: A Retrospective Study - Widiastuti, Ida Ayu Kade Sri; Sari, Rita Puspa; Ruminem, Ruminem (Jurnal Kesehatan Pasak Bumi Kalimantan, 2025)
The COVID-19 pandemic has significantly affected children's lifestyles, including their sleep patterns, which are vital for growth and development. Exclusive breastfeeding (EBF) is believed to positively influence children's sleep quality through its bioactive components. This study aims to compare the effects of exclusive breastfeeding on children's sleep quality during and after the COVID-19 pandemic in Samarinda. This retrospective comparative study involved 372 children aged 0-2 years. Data were collected through parent interviews and sleep quality assessment using Children’s Sleep Habits Questionnaire (CSHQ). Chi-square tests and odds ratios (OR) were used to analyze differences in sleep quality between children who were exclusively breastfed and those who were not, during and after the pandemic. During the pandemic, children with exclusive breastfeeding had 7.22 times higher odds of good sleep quality compared to those without (p=0.00). After the pandemic, this odds ratio decreased to 1.45 and was not statistically significant (p=0.123). This indicates that the impact of exclusive breastfeeding on sleep quality was stronger during the pandemic than after. Exclusive breastfeeding plays a crucial role in supporting children's sleep quality during the COVID-19 crisis, but its influence diminishes with age and normalization of daily routines. Environmental factors and parenting practices become the primary determinants of children's sleep quality post-pandemic. Education and nursing interventions should focus on parenting patterns and managing children's sleep routines after the pandemic.